RECOGNIZING SPEECH ACTS OF REFUSALS - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2010)
This article discusses how a speaker should recognize refusals of requests in English. The choices of whether or not uttering refusals or the selection of expressions to be used in uttering the refusals could disrupt or maintain the interaction with language in progress. Therefore, a discussion on related theories needs to be presented in this article in the effort as to provide insights of significant aspects in uttering refusals of requests. It is a descriptive discussion that it only presents arguments on speech acts of refusals by reviewing its related theories. Speech Acts of Refusals  ( SARs ) may gain much attention in the discussion since it is the central focus of the discussion. Conversational Principles and Face Threatening Acts of Politeness Theory are also touched because they also help the speaker to think of how to utter refusals of requests. Thought Patterns, on another side, culturally and pragmatically color the manner a speaker should utter refusals of requests in a given cultural context. Finally, the discussion also presents the degree of sensitiveness to social status, social distance and gender between the interlocutors in expressing refusals since those factors influence the choices of expressions of refusals.Key words: Speech Acts of Refusals  ( SARs ) , Conversational Principles, FTA in Politeness Theory, Thought Patterns.